A year in the life of a Brazilian professional female road cycling team - Part II: Nutritional and clinical outcomes - Campos-Ferraz, P.; Barreto, G.; Farias de Oliveira, L.; Saito, T.; Klosterhoff, R.; Lopes Perim, P. H.; Dolan, E.; Rodrigues Pereira, R. M.; Lima, F.; Saunders, B. (Journal of Science and Cycling, 2019)
Background: Professional female cyclists undertake intense training, and the demands of this training must be met by adequate nutritional intake. This is particularly relevant for professional teams who train and compete all year round, as they can cover up to 18 000 km (Sanders et al., 2019). Energy availability (EA) refers to the amount of energy available for basic physiological processes, once the demands of training have been met (Loucks et al., 2011). Low EA (often defined as <30 kcal/kgLBM·day), can lead to a wide range of detrimental physiological and performance consequences (as described in the Relative Energy Deficiency in Sport model (Mountjoy et al., 2014)) with menstrual dysfunction and compromised bone health in particular known to be affected As such, adequate energy (and nutrient) intake is essential to protect the health and performance of top-level cyclists. In this investigation, we monitored the nutritional habits of a professional Brazilian female cycling team throughout a competitive season and measured several outcomes related to REDs.